Pengembangan Lembar Kerja Siswa Materi SPLDV untuk Meningkatkan Hasil Belajar Siswa Melalui Pendekatan Matematika Realistik - Taniu, Deni; Hijriani, Lailin; Kehi, Yohanes Jefrianus; Siahaan, Meiva Marthaulina Lestari; Fitriani, (Media Pendidikan Matematika, 2025)
This research is motivated by the lack of worksheets development (LKS) at school based on the Realistic Mathematics Approach (RMA), which has resulted in low student mathematical abilities, especially in solving system of linear equations in two variables. This research aims to produce valid, practical, and effective Student Worksheets (LKS) based on the Realistic Mathematics Approach (RMA) for algebra. The research aimed to improve students' mathematical abilities, which will impact student learning outcomes. The research type is research and development (R&D) using the 4-D model. The target population of this study was 20 students of class VIIIA at Junior High School Neonbat. The instruments used were expert validation sheets, student response questionnaire sheets, and pretest and posttest questions. The results of the study showed that the quality of the student worksheets met the validity criteria, with an average value of 84.78% in the very valid category. The results of the LKS practicality questionnaire showed an average score of 90.6% in the very practical category. While in terms of effectiveness, it met the effective criteria. The average individual score for the pretest results was 24.5. However, it increased after using the student worksheet as indicated by the posttest results with an average value of 79.5. The percentage of classical completion based on the posttest results was 80%, which is included in the effective category. So that, the student worksheet for algebra material through realistic mathematics approach met the criteria of valid, practical, and effective.